Construction of stabilized bulk-nano interfaces for highly promoted inverse CeO2/Cu catalyst - Han Yan (Nature Portfolio, 2019)
Cu-CeO2 has been considered as promising alternative to Cu-Zn-Al catalyst for water-gas shift (WGS) reaction, but it still suffers from low activity caused by Cu sintering. Here, the authors develop inverse CeO2/Cu catalyst with remarkable activity and stability in WGS via construction of stabilized bulk-nano interfaces.